Early pubertal maturation and risk of childhood asthma: A Mendelian randomization and longitudinal study. Issue 4 (27th August 2019) - Chen, Yang‐Ching; Fan, Hsien‐Yu; Yang, Chen; Lee, Yungling L.
Abstract: Background: Studies on early puberty and incident asthma have reported inconsistent results and are mainly performed in females. In this longitudinal study, we investigated the causal relationship between pubertal maturation and asthma through Mendelian randomization (MR) and explored the joint effect of overweightness and early pubertal maturation on asthma. Methods: We used data from the Taiwan Children Health Study with longitudinal follow‐ups of 2991 children aged 11‐17 years. Six puberty‐related single‐nucleotide polymorphisms (combined into a weighted allelic score) were used to yield genetic instrumental variables for early puberty. Early pubertal maturation was defined as reaching a certain pubertal stage earlier than the median age for that stage. Incident asthma cases were calculated by excluding children with a history of asthma prior to that age. Results: The results of MR analysis revealed that early pubertal maturation was associated with active asthma (OR = 1.18; 95% CI: 1.08‐1.28); this effect was significant in male children. Early pubertal maturation significantly increased the risk of incident asthma outcomes at 12 and 17 years of age in both sexes (hazard ratio = 2.15; 95% CI: 1.21‐3.84). Taking non‐overweight and non–early puberty children as the reference group, we observed a synergistic effect of overweightness and early pubertal maturation on asthma risk (OR = 1.08; 95% CI: 1.04‐1.11) in children of both sexes. Conclusions: Early screening and intervention for obesity are recommended to prevent future early pubertal onset and asthma occurrence. Abstract : Through Mendelian randomization analysis, we discovered that early pubertal maturation led to asthma in 2991 children from Taiwan Children Health Study. Early pubertal maturation significantly increased the risk of incident asthma outcomes at 12 and 17 years of age in both sexes. Childhood overweight and early pubertal maturation exerted synergistic effect on asthma risk. [Colour figure can be viewed at wileyonlinelibrary.com]